Corruption in Russian society as a specific form of social interaction - V. Kasyanov, Valery (2018)
It is considered the phenomenon of corruption in modern Russian society, the causes and basis of its existence in this article. It was concluded that the key to the institutionalization of corruption in Russian society are the processes of legitimization and ritualization of corruption practices based on the results of our research. The corruption becomes one of the negative factors in regulating social relationships in contemporary Russian society due to this practice. The corruption experience and corruption culture of the population were showed in this article. There are the assessments and attitudes towards corruption, its manifestations in the mass consciousness of the population in this article. We identified the spheres where that phenomenon is more intensively. Also we determined the specific of the manifestation of corruption in the national subjects of the Russian state. The authors concluded that corruption is most clearly manifested in the situation of degradation of the value-normative space.